STRATEGI MARKETING POLITIK PARTAI SOLIDARITAS INDONESIA (PSI) PADA SEGMENTASI PEMUDA DI KOTA PEKANBARU - Rifdah Hayani Nasution; Belli Nasution (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
The purpose of this study was to determine the political marketing process of the Indonesian Solidarity Party in the segmentation of youth in Pekanbaru in determining party orientation. And to find out the political marketing process of the Indonesian Solidarity Party in the face of the 2019 legislative elections in Pekanbaru City in the process of finding and developing supporters. The political marketing theory approach used was owned by Lees-Marshment to see the process of determining party orientation and that of Adman Nursal to see the party develop supporters and voters on the segmentation of youth in Pekanbaru.                This study uses a descriptive qualitative research method with a purposive technique. From data analysis, it can be concluded below in the political marketing process ahead of the 2019 election, the Indonesian Solidarity Party is a sales-oriented party (SOP), this is based on the foundation of the party and programs that are not formed through a market research process but after political products are formed mapping has only been carried out and acts of persuasion to prospective voters are deemed appropriate. The Indonesian Solidarity Party does not have specifications in mapping and voter targets because millennial is not homogeneous so it cannot be classified as only one group, in the process of delivering products PSI has not been able to balance 3 approaches simultaneously, namely directly, through the media, and influential figures or groups , because PSI is still focusing on the use of FGDs and social media but has not yet taken the process directly to the grassroots and there are not many influential figures possessed by the PSI so that the PSI does not have closeness to groups that are able to support the PSI vote in the upcoming elections. The marketing process carried out by PSI ahead of the 2019 election is still relatively low, so that the existence of the PSI in the upcoming 2019 election is only for existence but cannot get a significant enough vote even though they are sure of that. Keywords: Political Marketing, Indonesian Solidarity Party, 2019 Election.